Peers at Work - a Brief Overview of the Literature on Peer Effects at the Workplace and the Policy Implications - Clara Welteke (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Individuals do not exist in isolation but are embedded within networks of relationships, such as families, coworkers, neighbors, friendships or socioeconomic groups. While there is a long tradition in sociology and anthropology focusing on theimportance of social structure, norms and culture, economists have long ignored social influences on individual behavior. Even though social influences may play an important role in the evaluation of policies, economic evaluations are typicallyfocused on the central question how individuals independently respond to financial incentives. However, economic reforms or the introduction of new policy instruments are likely to affect individuals not only directly by the change in financial incentives, but also indirectly by a change in the behavior of the social environment. At the workplace, one can distinguish four contexts where peer effects may be relevant factors in explaining the observed outcomes; these are (a) job search and employment probabilities; (b) fertility, parental leave and female labor supply; (c) productivity and work place behavior; and (d) retirement and pension plan decisions. Consequently, it is of large importance to understand and predictsocial interaction effects in these four areas of research and comprehend the implications for economic policy. In the following, I will give an overview of the existing literature in each of the contexts where peer effects at work may evolve, after briefly discussing the challenges associated with the empirical analysis of peer effects.
Keywords: 330